Exploring Consumption of Ultra‐Processed Foods and Diet Quality in the Context of Popular Low Carbohydrate and Plant‐Based Dietary Approaches - De La Motte, Kayla‐Anne Lenferna; Campbell, Jessica L; Zinn, Caryn (Wiley, 2024)
This study investigates diet quality across four popular dietary patterns: Ketogenic Diet, Low‐Carbohydrate Healthy‐Fat, Vegetarian, and Vegan, employing the NOVA and Human Interference Scoring System (HISS) classification systems. Utilizing a modified Food Frequency Questionnaire (FFQ) and analyzing 168 participants' dietary habits, the research identifies notable differences in dietary quality among the dietary patterns. While all groups reported lower consumption of UPFs than the general population, plant‐based diets demonstrated higher UPF consumption than ketogenic and low carbohydrate diets. The study reveals that both NOVA and HISS effectively identify UPFs, with significant differences observed at various processing levels, except for UPFs where both systems showed similarity. This research contributes to the detailed understanding of diet quality within popular dietary patterns, highlighting the importance of considering food processing in dietary choices and the need for ongoing research to further elucidate the health implications of different types of UPFs.
Keywords: 32 Biomedical and Clinical Sciences; 3210 Nutrition and Dietetics; Complementary and Integrative Health; Dietary Supplements; Nutrition; Oral and gastrointestinal; 0908 Food Sciences; 1111 Nutrition and Dietetics; 3006 Food sciences; 3210 Nutrition and dietetics